Uncoupling language and religion - Mignon, Laurent, 1971- (Boston)
xxxiii, 216 sayfa
Keywords: “This book is an invitation to rethink our understanding of Turkish literature as a tale of two “others.“ The first part of the book examines the contributions of non-Muslim authors, the “others“ of modern Turkey, to the development of Turkish literature during the late Ottoman and early republican period, focusing on the works of largely forgotten authors. The second part discusses Turkey as the “other“ of the West and the way authors writing in Turkish challenged orientalist representations. Thus this book prepares the ground for a history of literature which uncouples language and religion and recreates the spaces of dialogue and exchange that have existed in late Ottoman Turkey between members of various ethno-religious communities.“ --